Association between neutrophil to lymphocyte ratio and mortality among community acquired pneumonia patients: a meta-analysis - Alzoubi, Osama; Khanfar, Asim (Monaldi Archives for Chest Disease, 2021)
The neutrophil to lymphocyte ratio (NLR) is an emerging biomarker used in the prognosis of many conditions. We aimed to conduct a meta-analysis to assess the prognostic accuracy of the NLR in determining mortality in patients with community acquired pneumonia (CAP). The PubMed, EBSCO, and Scopus databases were searched to find all relevant articles; 10 articles with 5220 patients were included. The pooled area under the curve (AUC) of NLR admission levels to predict 30-Day mortality of CAP patients was 0.706; 95% CI (0.631 to 0.781), while the pooled AUC of NLR levels taken at 3-5 days was 0.882; 95% CI (0.818 to 0.945). Meta analysis also showed a significant difference in the NLR between the survivors and 30-day non-survivors. This difference was greater when NLR levels were taken at 3-5 days; standardized mean difference (SMD) = 1.646; 95% CI (0.451 to 2.840) compared to NLR levels at admission SMD = 1.139; 95% CI (0.514 to 1.764). These results show that the NLR has potential to be incorporated in the routine assessment and stratification of CAP patients, especially in the early-stage evolution (3-5 days), keeping in mind the availability and cost effectiveness of this test.